Pembangunan Aplikasi Pengelolaan Data pada Rumah Sakit Berbasis Web - Sara Amelia Rosadi; Andika Wirawan; Sendy Ferdian Sujadi (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Hospital has a variety of facilities and services. Every day there are transactions recorded by the hospital in the form of documentation such as excel. Over time, if the transactions increase, the files that will be stored will be more and more large. Therefore, a website was created that can make it easier to manage data from these files. The web application is created using PHP and integrates with the MySQL database. The main module of the web application created is to import data from an excel file. The expected results from making this website are to make it easier for employees to manage data and view information in the form of tables or graphs. Data collection methods using observation, through interviews with the person in charge from hospital by giving a questionnaire about the interface of the application. Assessment of the results of interface improvements using a questionnaire from Post-Study System Usability Questionnaire version three, totalling 16 questions. The purpose of the User Interface and User Experience analysis is to assess and serve as a guide for improving the display that has been made whether it is in accordance with the standards requested by the hospital.